Barriers to the Integration of Venezuelan Migrants and Refugees in Colombia (2023)
Integration migrants has become a central challenge and opportunity for public policy in the medium term, to mitigate the impacts and maximize the benefits. This study explores the factors that enhance or reduce barriers to accessing opportunities. Based on data from the Migration Pulse (MP) survey, our analysis finds that access to information, contact networks, and documents for migratory status regularization play an important role in facilitating access to services and improving this group’s employability. Thus, the findings show the interrelationship between integration policies and their complementarity, such as those related to healthcare access and the regularization process. Overall, the results provide evidence supporting the convenience of place-based policies.